An evaluation of resources efficiency in University Malaysia Pahang using data envelopment analysis (DEA) method - Nurul Aqilah, Rahman (2015)
This research study involves DEA in order to determine the performance level of 9 faculties in University Malaysia Pahang (UMP). The aim of the research is to estimate and analyse the efficiency in (UMP) for the academic year 2014. Using the number of students enrolled, number of lecturer and lecture room provided as inputs, and the total number of graduate student and a number of publication as outputs. Technical efficiency was used to estimate efficiency. And by using DEA it is possible to get a general execution measure performance through the examination of a gathering of decision units. Objective of this study is to identify the efficiency variable influencing faculty’s performance and to evaluate the efficiency of faculties’ performance using DEA. Recently, in many studies DEA method has been use to evaluate performance of university. The result showed that UMP faculty obtained average scale efficiency 0.86 and only three UMP faculties get the optimum size.